Not Norman : a goldfish story - Bennett, Kelly; Jones, Noah (Noah Z.) (Cambridge, MA : Candlewick Press, 2005)
As a boy attempts to convince someone else to take his disappointing pet, he learns to love Norman the goldfish himself.
School Library Journal
Publisher's Weekly
Booklist
Kirkus Reviews
2.4
K-3
Keywords: Pets -- Juvenile fiction; Goldfish -- Juvenile fiction; Friendship -- Juvenile fiction; Pets -- Fiction; Goldfish -- Fiction; Friendship -- Fiction; Pets -- Fiction; Goldfish -- Fiction; Friendship -- Fiction